Just a little blue - Runton, Andy (New York Scholastic / Graphix, 2020)
Owly learns that sometimes you have to make sacrifices and work at things that are important, especially friendship.
2.0
1-4
Keywords: Owls -- Comic books, strips, etc. -- Fiction; Birds -- Comic books, strips, etc. -- Fiction; Friendship -- Comic books, strips, etc. -- Fiction; Owls -- Comic books, strips, etc. -- Fiction; Birds -- Comic books, strips, etc. -- Fiction; Friendship -- Comic books, strips, etc. -- Fiction; Graphic novels; Animal fiction